2020
DOI: 10.1371/journal.pntd.0007981
|View full text |Cite
|
Sign up to set email alerts
|

Test accuracy of polymerase chain reaction methods against conventional diagnostic techniques for Cutaneous Leishmaniasis (CL) in patients with clinical or epidemiological suspicion of CL: Systematic review and meta-analysis

Abstract: Background Molecular diagnostic tests, notably polymerase chain reaction (PCR), are highly sensitive test for Leishmania detection, which is especially relevant in chronic cutaneous lesion with lower parasite load. An accurate diagnosis is essential because of the high toxicity of the medications for the disease. Nevertheless, diagnosis of cutaneous leishmaniasis (CL) is hampered by the absence of a reference standard. Assuming that the PCR-based molecular tools are the most accurate diagnostic method, the obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…The high sensitivity and specificity of developed Pan- Leishmania qPCR suggests this method could be used to better diagnose CL infected by L. major and VL infected mostly by L. donovani and L. infantum in China. Indeed, 20 skin lesion samples from clinically confirmed CL patients and 20 bone marrow and/or PBMC samples from clinically confirmed VL patients were tested by this new qPCR assay as all positive, with 100% sensitivity which is higher than previously reported for qPCR detection (69.23–98.53%)(Khosravi et al, 2012 ; El-Beshbishy et al, 2013 ) or microscopy smears (90–98%) (Mesa et al, 2020 ). We also confirmed the specificity of the assay not to cross-react with 11 clinical samples from patients with other infections with malaria, brucellosis, dengue fever and blood samples from five healthy volunteers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The high sensitivity and specificity of developed Pan- Leishmania qPCR suggests this method could be used to better diagnose CL infected by L. major and VL infected mostly by L. donovani and L. infantum in China. Indeed, 20 skin lesion samples from clinically confirmed CL patients and 20 bone marrow and/or PBMC samples from clinically confirmed VL patients were tested by this new qPCR assay as all positive, with 100% sensitivity which is higher than previously reported for qPCR detection (69.23–98.53%)(Khosravi et al, 2012 ; El-Beshbishy et al, 2013 ) or microscopy smears (90–98%) (Mesa et al, 2020 ). We also confirmed the specificity of the assay not to cross-react with 11 clinical samples from patients with other infections with malaria, brucellosis, dengue fever and blood samples from five healthy volunteers.…”
Section: Discussionmentioning
confidence: 84%
“…An alternative immunological based assay is to detect antibody anti Leishmania rK39 antigen with sensitivity of 67–100% (Pagliano et al, 2016 ; van Griensven and Diro, 2019 ), however, this immunological assay is unable to differentiate between current and historical infection (Saliba et al, 2019 ). Regular PCR is sensitive, but cannot be used to monitor the parasite load during medical treatment, and so is not appropriate for ongoing patient/disease management, or evaluating the treatment efficacy (Mesa et al, 2020 ). Therefore, it is urgently needed to develop a diagnostic method with high sensitivity and quantitative measurement of infected parasite for clinical physicians.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to microscopy, it is well-known that molecular tools can provide rapid, sensitive, accurate detection, quantification, and species identification depending on the target and design used [ 47 49 ]. In this study, we, therefore, compared the performance of well-known (SSU, kDNA) and less common (SL) PCR targets for CL detection.…”
Section: Discussionmentioning
confidence: 99%
“…DNA isolates of the SS samples were subjected to a conventional PCR targeting a 350 bp fragment of the ITS-1 gene ("ITS PCR"), based on El Tai et al [22] as described before [30]. In short, the samples were screened in duplicate with a 15 μl reaction mix consisting of 0.5 μM of each primer (LITSR 5'-CTGGATCATTTTCCGATG-3' and L5.8S 5'-TGATACCACTTATC GCACTT-3' (Invitrogen, Life Technologies, Belgium)), 0.2 mM dNTP (GE Healthcare Lifescience, Belgium), 1X QIAGEN PCR Buffer (Qiagen, Belgium), 0.04 U/μl HotStarTaq DNA polymerase (Qiagen) and 1.5 μl of 1/10 diluted DNA extract.…”
Section: Conventional Its-1 Pcrmentioning
confidence: 99%
“…Another limitation of this study was that a parasitologically confirmed diagnosis was difficult to obtain. The sensitivity of microscopy, the gold standard used in the routine programme, varies between 70 and 90% [36,38,[46][47][48]. There are CL lesions in which parasites cannot be found, since the yield of organisms is variable and sometimes zero, especially when the period between the first appearance of the lesion and the diagnosis is relatively long, or the CL presentation is atypical (37,48).…”
Section: Discussionmentioning
confidence: 99%